Investigation into ageing and the effect of hydrated lime on mastics and mixture ageing - Alfaqawi, Rami Mohammed S. (2018)
Age hardening of bitumen is one of the key factors determining the lifetime of an asphalt pavement. When the bitumen is excessively aged, the asphalt mixture will become brittle and its ability of supporting traffic-induced stresses and strains may significantly reduce, which can easily cause some cracking damage to the bound layer of a pavement. As bitumen is always in contact with mineral fillers in asphalt mixtures, the mechanisms of oxidative ageing of binders are significantly influenced by the physical and chemical interaction between fillers and the bitumen. For a long while, attempts to solve the ageing problem of asphalt binder by various methods, including polymer modification, nano-particle enhancement or functional improvement have been undertaken. Hydrated lime is one of many potential additives used in bitumen to improve the performance of asphalt mixtures. Hydrated lime in hot mix asphalt creates multiple benefits. A considerable amount of information exists in the literature on hydrated lime’s ability to control water sensitivity and its well-accepted ability as an anti-stripping agent to inhibit moisture damage. However, recent studies have shown that lime acts as an active filler and anti-oxidant. These properties create multiple benefits for pavements. Although the majority of research on the use of hydrated lime in asphalt mixtures has been carried out in the USA, the beneficial effects of hydrated lime have also been reported worldwide especially in Europe. In the UK, the use of hydrated lime only started in the early 2000’s and still needs a lot of research into its effect on the traditionally used asphalt materials in the UK pavement industry. This research primarily focuses on an in-depth investigation of bitumen ageing mechanisms and evaluation. Furthermore, this research aims to investigate the advantages of using hydrated lime to mitigate ageing in bitumen mastics and asphalts mixtures as a whole.